Lands and "Sertões" in Brazilian thought: a political sociology in the periphery - Maia, João Marcelo Ehlert (Universidade Estadual Paulista / UNESP, 2008)
This article seeks to prove that is possible to deal with Brazilian thought (and the spatial theme, in particular) as a form of peripheral social theory. I analyze Euclides da Cunha’s texts about Amazônia and Oliveira Vianna’s inquiry about the Center-South of Brazil. By choosing two representative figures of our republican imagination, both oriented by unique theoretical perspectives, my goal is to show how space emerges in these texts not as a landscape or a simple representation of local rural areas, but as traces of a spatial living of brazilian people which can be observed in different places of our social worlds. I suggest that is possible extract from the texts the main themes of this kind of living, which form the core of a political sociology: the experience of vagrancy as a basic condition of lower classes, the incapacity of liberalism to function as a guide for social relations, violence as an expression of sociability an the idea that Brazil was formed as a society in motion. Therefore, far from being just a geographic element, space can be seen as a privileged form of cognition.